2005
DOI: 10.5713/ajas.2005.957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Urea Treatment and Soybean Meal (Urease) Addition on the Utilization of Wheat Straw by Sheep

Abstract: The effect of ammoniation with urea and with soybean meal (SBM) as a source of urease on the nutritive value of wheat straw was evaluated in sheep. Twenty-four male Najdi lambs were used in a 3×2 factorial design, in which the animals were allocated to three straw treatments: 0% urea-treated (NT), 6% urea-treated (UT) and 2.2% urea-supplemented (US) straws. Each straw treatment was either supplemented or non-supplemented with 70 g SBM kg -1 straw during the treatment time with urea, giving a total of six straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
9
0
5
Order By: Relevance
“…As expected, total forage N content was increased significantly in all experiments by urea application as noted in previous studies (Aregawi et al., ; Hanafi, el Khadrawy, Ahmed, & Zaabal, ; Kraidees, ; Mehra et al., ; Milad et al., ; Souza & dos Santos, ; Vieira Pires, Giordano Pinto De Carvalho, & Oliveira Ribeiro, ). All HFF treatments with urea alone or combined with other chemical agent resulted in final CP values above 60–80 g/kg DM.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…As expected, total forage N content was increased significantly in all experiments by urea application as noted in previous studies (Aregawi et al., ; Hanafi, el Khadrawy, Ahmed, & Zaabal, ; Kraidees, ; Mehra et al., ; Milad et al., ; Souza & dos Santos, ; Vieira Pires, Giordano Pinto De Carvalho, & Oliveira Ribeiro, ). All HFF treatments with urea alone or combined with other chemical agent resulted in final CP values above 60–80 g/kg DM.…”
Section: Discussionsupporting
confidence: 88%
“…Higher ADF values also were observed by Dias-Da-silva and Sundstøl (1986), Mehra, Dass, Verma, and Sahu (2001) and Kraidees (2005) who studied the effect of urea ammoniation on the nutritive value of different straws. Although it is not clear how the urea treatment could result in an increase in ADF values in this study, it may have to do with swelling of the fibre as indicated by Kumar, Kamra, Agarwal, and Chaudhary (2009).…”
Section: Fibre Fractionsmentioning
confidence: 71%
See 3 more Smart Citations